Analisis Regulasi Hukum Dan Implikasi Terhadap Penegakan HAM Di Pulau Rempang - Puji Widiyanti; Layla Rosida; Muhammad Rifai; Keisha Angeli Saputra; Ali Maskur (LPPM Universitas HKBP Nommensen, 2023)
This research examines the social and economic impacts of the Rempang Eco City development project on Rempang Island, Batam City, which involves the Batam Business Agency and the private company PT Makmur Elok Graha. The background to the problem involves a conflict between local residents and joint forces that occurred on September 7 2023, in connection with a land dispute and the relocation of residents. The research objective is to analyze this conflict in a social, economic and human rights context, and identify its implications for local communities. Another of purpose is to examine the human rights enforcement in Indonesian legal and political system. This is done by studying the legal basis of human rights, the process of proliferation of human rights discourse, and the actual controversies of human rights enforcement. The research methodology includes field data collection through observations and interviews, as well as analysis of project-related documents. The research results show that this conflict has had a significant impact on the economic and social life of the Rempang community, especially fishermen. In addition, there are tensions between historical, cultural and land claim aspects and project planning. The research conclusion is that this conflict must be seen as a serious problem involving various dimensions, and its resolution requires attention to human rights, community participation, and recovery for victims, while considering the historical and cultural values ​​involved in this case.